ANNOTATING TRANSLATION AS A MEANINGFUL METACOGNITION-ORIENTED PRACTICE IN THE TRANSLATION CLASSROOM - Costa, Cynthia Beatrice; Lourenço da Silva, Igor Antônio (Revista de Letras, 2023)
Translating is a cognitively complex activity aimed at tackling an ill-defined problem: selecting only one viable rendition in the target language from a series of multiple viable choices for a given text in a source language (PYM, 2003). Developing the ability to perform such an activity with a reasonable speed and justified confidence (PYM, 2003) may profit from learning how to perform a parallel activity, i.e., annotating, as a fruitful avenue toward metacognition (ALVES, 2005; SHREVE, 2006) and the articulation thereof. We argue in this article that annotating (or commenting) can be an effective practice in the translation of any genre and play a relevant role from the beginning of translator’s training. Building both on a review of expertise (ERICSSON, 2001) and translation pedagogy (GONÇALVES, 2020; ESQUEDA, 2020) and on our own teaching experience, we suggest that annotating translation can: a) be performed as part of deliberate practice (in the broad sense) during the translation process, b) honestly inform students and trainers about the difficulties faced during the process, c) invite useful feedback, and d) potentially leverage students’ metacognition.